CHOROIDAL DEGENERATION IN BIRDSHOT CHORIORETINOPATHY. Issue 4 (April 2015) - Young, Mei; Fallah, Nader; Forooghian, Farzin
Abstract : Purpose: The purpose of the study was to determine if progressive choroidal changes occur in birdshot chorioretinopathy (BSCR). Methods: Retrospective chart review of all patients with BSCR who were seen over a 3-year period. Controls consisted of healthy age-matched and gender-matched patients. Choroidal thickness at baseline and final follow-up visit was measured with the use of optical coherence tomography. Results were analyzed using univariate and multivariable statistical models. Results: A total of 11 patients (22 eyes) with BSCR were identified. The majority of BSCR eyes (86%) had clinically inactive disease. Follow-up ranged from 2 months to 27 months. Mean age was 55 years. Patients with BSCR had significantly thinner choroid compared with controls ( P < 0.001). Furthermore, the rate of choroid thinning for patients diagnosed with BSCR (2.68 μ m per month) was significantly higher than that of controls (0.27 μ m per month) ( P = 0.003). There was no statistically significant difference in the rate of choroidal thinning between the two eyes of patients with BSCR ( P = 0.859), indicating that the choroidal thinning was symmetrical. Conclusion: Despite having clinically inactive uveitis, eyes with BSCR can develop progressive choroidal thinning. The clinical relevance of this choroidal thinning, or degeneration, remains to be fully elucidated. Abstract : The authors used optical coherence tomography to measure choroidal thickness and the rate of choroidal thinning in patients with birdshot chorioretinopathy. Patients with birdshot chorioretinopathy were found to have thinner choroid and an increased rate of choroidal thinning compared with normal controls, despite having clinically inactive uveitis.